Money-prospects of Cryptocurrencies - A Bibliometric Review - Muhammad Suleman Afzal; Arshad Ali Bhatti (Islamic Banking and Finance Review, 2021)
The status of the money-prospects of cryptocurrencies in both conventional and Shari’ah based literature remains hotly debated and largely indecisive. We apply/used the bibliometric approach to review the literature on/regarding the money-prospects of cryptocurrencies. We selected 264 articles published during the years 2011-2021 from Web of Science (WoS) through systematic screening to explore their influential and intellectual aspects. Bibliometric citation analysis was conducted to present/identify influential research categories, leading authors, top articles, prominent countries, and major journals within the sample. We also highlighted the trend of annual scientific production to show sustained growth in the area under research. Furthermore, keyword analysis and bibliometric coupling analysis were applied/carried out to generate networks to highlight the intellectual aspects of the money-prospects of cryptocurrencies. We used the networks of emerging themes and main clusters to conduct content analysis further. We included and reviewed studies which discussed the money-prospects of cryptocurrencies in the light of Shari’ah precepts in relevant clusters. We also identified potential future research areas (cluster-wise). Theis study helps the researchers to understand the evolution, dimensions, and emerging themes regarding the money-prospects of cryptocurrencies.Keywords   Bibliometric, Bitcoin, Cryptocurrencies, Islam, Money